Avaliação do uso do ultrassom para a remoção de hidróxido de cálcio em cavidades simuladas de reabsorção radicular interna - Klamas, Vanessa Cavassin (2020)
The aim of this study was to verify the effectiveness of the ultrasound (US) in the removal of calcium hydroxide paste (CH) in simulated internal root resorption cavities (IRR). Ninety-six uniradicular, single-canal human anterior teeth were selected. The canals were prepared with a Reciproc® R50 (50 / .05), the roots were cleaved in the buccolingual direction and cavities were created with a spherical burr 5 mm from the root apex to simulate an IRR. The two halves of the root were joined with cyanoacrylate glue and the canals filled with CH paste. The irrigation protocol used to remove the paste was 3 cycles of 20 seconds of stirring 2 ml of 2.5% sodium hypochlorite, 3 cycles of 20 seconds of stirring 2 ml of 17% EDTA, followed by final washing with 10 ml of distilled water. The specimens were randomly divided into eight experimental groups (n = 12), according to the activation direction and depth of insertion of the ultrasonic insert for removing of CH paste in: MD1 - working length (WL) -1 mm mesio distal (MD) direction; BL1 - WL-1 mm in the bucco lingual (BL) direction; MD3 - WL-3 mm in the MD direction; VL3 - WL-3 mm in the VL direction; MD5 - WL-5 mm in the MD direction; VL5 - WL-5 mm in the VL direction; C + - positive control group, canal filled with CH paste; C- negative control group, canal without CH paste. All samples were submitted to the irrigation protocol except for the control groups. The roots were cleaved and optical microscopy (OM) (with 20x magnification) and scanning electron microscopy (SEM) (with 100x magnification) images were performed to evaluate the remnant of CH paste. Two calibrated examiners evaluated the images obtained following previously established scores. Data were compared using Kruskal Wallis, Mann Whitney U and Wilcoxon statistical tests, with a significance level of 5%. There was a statistically significant difference between the experimental groups and the C- group in comparison to the C+ group (p <0.05) but there was no difference between the experimental groups in the CH paste removal capacity (p> 0.05). In the comparison between the two evaluation methods, MO and SEM, there was a statistically significant difference, where the greater amount of CH remnant was observed with SEM. It can be concluded that the protocols used were effective in removing CH paste from simulated IRR.